Pb(ii) adsorption from aqueous solution by an aluminum-based metal organic framework–graphene oxide nanocomposite. Issue 9 (9th April 2021) - Chowdhury, Tonoy; Zhang, Lei; Zhang, Junqing; Aggarwal, Srijan
Abstract : The composites of metal–organic frameworks (MOF) and graphene oxide (GO) have demonstrated strong potential in removing Pb(ii ) ions from industrial wastewaters. Abstract : The composites of metal–organic frameworks (MOF) and graphene oxide (GO) have demonstrated strong potential in removing organic and inorganic contaminants from industrial wastewaters. Motivated by the promise of these emerging nanocomposites, here we report for the first time the adsorption performance of an aluminum-based MOF (MIL-53(Al)) and GO nanocomposite for Pb(ii ) removal from aqueous solutions. The developed GO-MIL-53(Al) nanocomposites exhibited a large surface area (∼1300 m 2 g −1 ) with abundant active sites, and demonstrated rapid (<30 min to achieve equilibrium adsorption) and high Pb(ii ) removal with an equilibrium adsorption capacity of 232 mg g −1 at room temperature. The adsorption kinetics and thermodynamics analyses of the Pb(ii ) adsorption data indicated that the adsorption process followed the pseudo-second-order and Langmuir isotherm models, respectively. Pre and post-adsorption FTIR data illustrated that after adsorption Pb(ii ) ions may be transformed into the corresponding hydroxide and oxide salts owing to the interaction with oxygen and hydroxyl groups in the GO-MIL-53(Al) nanocomposite. Furthermore, the GO-MIL-53(Al) nanocomposite exhibited consistent Pb(ii ) removal efficiency for selected natural water samples, suggesting its potential in removing Pb(ii ) from complex natural water and wastewater matrices.